Dinamika Amonium dan Nitrat Pada Lahan Sawah Semi Organik untuk Tanaman Padi Lokal dan Hibrida di Subak Jatiluwih Kabupaten Tabanan - KHOTIMAH, KHOSNUL; SUWASTIKA, ANAK AGUNG NGURAH GEDE; ATMAJA, I WAYAN DANA (Agrotrop : Journal on Agriculture Science; Vol 10 No 1 (2020)DO - 10.24843/AJoAS.2020.v10.i01.p05, 2020)
Dynamics Of Ammonium And Nitrate In Semi Organic Rice Fields For Local And Hybrid Rice Plants In Subak Jatiluwih, Tabanan Regency. The study was conducted to determine the dynamics of ammonium and nitrate and time subsequent fertilization in paddy fields with local and hybrid rice. Soil and water samples in two replications were taken each the two paddy fields periodically, namely during the tillage (DTT), 0, 7, 14, 21, 28, 42, 56, 70, 84, 98, and 112 days after planting (DAP). Ammonium and nitrate levels were analyzed by Macro Kjeldahl method. The results showed that the dynamics of ammonium and soil nitrate were different in two rice varieties. The highest ammonium content of local rice at the age of 7 DAP rice and the highest nitrate content at age 14 DAP. Ammonium and nitrate levels are highest in hybrid rice fields at 28 DAP rice age. The lowest ammonium and nitrate levels in two different varieties of rice land, namely the lowest local rice varieties at the age 28 DAP, whereas in hybrid rice land at age of 98 DAP. The results of this study indicate that supplementation of urea can be carried out at the age of 21 and 98 DAP for local rice varieties, and at the age of 14 DAP and 42 DAP for hybrid rice varieties.